Depression biased non‐Hebbian spike‐timing‐dependent synaptic plasticity in the rat subiculum. (24th June 2014) - Pandey, Anurag; Sikdar, Sujit Kumar
<x xml:space="preserve">Abstract</x> Key points Spike‐timing‐dependent plasticity (STDP) is the induction of synaptic plasticity by coincident activity of pre‐ and postsynaptic neurons. In most of the excitatory synapses, an EPSP immediately followed by a back‐propagating action potential (bAP) enhances the synaptic efficacy, whereas the reverse weakens it. Contrary to the above observation, we demonstrate that, at the proximal excitatory synapses on the subicular pyramidal neurons, an EPSP immediately followed by a burst of bAPs weakens the synaptic strength, whereas the reverse strengthens the synapse in both bursting and regular firing neurons. This reverse STDP rule may have strong implications in synaptic integration and information outflow from the hippocampus. Interestingly, the mechanisms associated with synaptic depression using the same induction protocol were different in the two neuronal subtypes, being postsynaptic in the bursting neurons requiring NMDA receptor activity, but presynaptic in the regular firing neurons involving L‐type calcium channels. Abstract The subiculum is a structure that forms a bridge between the hippocampus and the entorhinal cortex (EC), and plays a major role in the memory consolidation process. Here, we demonstrate spike‐timing‐dependent plasticity (STDP) at the proximal excitatory inputs on the subicular pyramidal neurons of juvenile rat. Causal (positive) pairing of a single EPSP with a single back‐propagating action potential (bAP) after a time interval of 10 ms (+10 ms) failed to induce plasticity. However, increasing the number of bAPs in a burst to three, at two different frequencies of 50 Hz (bAP burst) and 150 Hz, induced long‐term depression (LTD) after a time interval of +10 ms in both the regular‐firing (RF), and the weak burst firing (WBF) neurons. The LTD amplitude decreased with increasing time interval between the EPSP and the bAP burst. Reversing the order of the pairing of the EPSP and the bAP burst induced LTP at a time interval of −10 ms. This finding is in contrast with reports at other synapses, wherein pre‐ before postsynaptic (causal) pairing induced LTP and vice versa. Our results reaffirm the earlier observations that the relative timing of the pre‐ and postsynaptic activities can lead to multiple types of plasticity profiles. The induction of timing‐dependent LTD (t‐LTD) was dependent on postsynaptic calcium change via NMDA receptors in the WBF neurons, while it was independent of postsynaptic calcium change, but required active L‐type calcium channels in the RF neurons. Thus the mechanism of synaptic plasticity may vary within a hippocampal subfield depending on the postsynaptic neuron involved. This study also reports a novel mechanism of LTD induction, where L‐type calcium channels are involved in a presynaptically induced synaptic plasticity. The findings may have strong implications in the memory consolidation process owing to the central role of the subiculum and LTD in this process.